Gilteritinib clinical activity in relapsed/refractory FLT3 mutated acute myeloid leukemia previously treated with FLT3 inhibitors. Issue 3 (7th January 2022) - Numan, Yazan; Abdel Rahman, Zaid; Grenet, Justin; Boisclair, Stephanie; Bewersdorf, Jan Philipp; Collins, Cailin; Barth, Dylan; Fraga, Martina; Bixby, Dale L.; Zeidan, Amer M.; Yilmaz, Musa; Desai, Pankil; et al.
Abstract: Gilteritinib is approved for the treatment of relapsed/refractory (R/R) acute myeloid leukemia (AML) with an FLT3‐mutation ( FLT3 mut+ ). However, the gilteritinib phase 3 ADMIRAL study (Perl et al NEJM 2019) was conducted prior to widespread adoption of either midostaurin as a component of standard intensive induction and consolidation or posttransplant FLT3 inhibitor maintenance. We performed a retrospective analysis using data from 11 US centers and where we identified 113 patients who received gilteritinib alone or as combination therapy for the treatment of R/R FLT3 mut+ AML. The composite complete remission (CR) rate (CRc, defined as CR + CRi + CR with incomplete platelet recovery [CRp]) was 48.7% ( n = 55). The CRc rate after treatment with gilteritinib in patients who were treated with only prior 7+3 and midostaurin with or without consolidation was 58% with a median survival of 7.8 months. Survival was longest in patients who obtained a CR, particularly a cMRD (clinical minimal or measurable residual disease) negative response; this remained significant after censoring at the time of stem cell transplant. The mitogen‐activated protein kinase pathway activating mutations that are known for gilteritinib resistance (NRAS, KRAS, and PTPN11) had lower CRc (35% vs. 60.5%) and lower median overall survival than patients' whose leukemia did not express these mutations (4.9 months vs. 7.8 months) (HR 2.4; 95% CI 1. 5.4) p value <.01.